Make It New Reshaping Jazz in the 21st Century - Beuttler, Bill (Lever Press, 2019)
As jazz enters its second century it is reasserting itself as dynamic and relevant. Boston Globe jazz writer and Emerson College professor Bill Beuttler reveals new ways in which jazz is engaging with society through the vivid biographies and music of Jason Moran, Vijay Iyer, Rudresh Mahanthappa, The Bad Plus, Miguel Zenón, Anat Cohen, Robert Glasper, and Esperanza Spalding. These musicians are freely incorporating other genres of music into jazz-from classical (both western and Indian) to popular (hip-hop, Ramp;B, rock, bluegrass, klezmer, Brazilian choro)-and other art forms as well (literature, film, photography, and other visual arts). This new generation of jazz is increasingly more international and is becoming more open to women as instrumentalists and bandleaders. Contemporary jazz is reasserting itself as a force for social change, prompted by developments such as the Black Lives Matter, #MeToo movements, and the election of Donald Trump.